Implementation of Vlog as a Learning Media for Tarjamah Syafawiyah in Training Students’ Arabic Speaking Skills - Nurul Izzah Amir (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to examine the use of vlogs in practicing students' Arabic speaking skills in the Tarjamah Syafawiyah course. Using a descriptive qualitative method, this study focuses on the observation and analysis of the process of making vlogs as a learning medium. The subject of the research was a student of UIN Raden Mas Said Surakarta class of 2019 who took part in the course. Data was collected through observations, interviews and documentation of student vlogs. The results of the study show that vlogs are effective in improving students' Arabic speaking skills, helping them be more confident and creative in using Arabic orally. Additionally, vlogs provide an opportunity for self-practice as well as receiving feedback from lecturers and classmates. Based on these findings, it can be concluded that vlogs are a useful learning medium for the development of speaking skills in the Tarjamah Syafawiyah course.Key words: Speaking skills, Arabic, Vlogs, Learning, Tarjamah Syafawiyah